Evaluación de polimorfismos en los genes th, dntbp1 y drd2 en pacientes esquizofrénicos - Vargas Luna, Andrea Samantha (2016)
Schizophrenia is a severe mental disorder that affects 1% of the world population, the development of the disease is related to both genetic and environmental factors. Through various linkage and association studies multiple schizophrenia susceptibility genes have been determined, such as the DRD2, TH and DNTBP1, which code for proteins such as D2 receptor, tyrosine hydroxylase and dysbindin-1 respectively. Mutations in these gen disrupt some neurotransmission pathways mainly the dopamine on e and altering migration, signaling and neuronal differentiation. In this study we focused in S311, Pro3129Pro, Taq1-B, CT, V81M, P1320, P1325 and P1763 polymorphisms in schizophrenic patients of Hospital Psiquiátrico Sagrado Corazón in Quito. Initially, only rs1079597 was not in Hardy Weingber equilibrium within the population. Subsequently, polymorphisms frequencies were present in both patients and control populations, although in some cases they had different genotypic distribution, no association can be attributed between clinical development of schizophrenia and the polymorphisms presence. Additionally, four polymorphisms were found in the amplify fragments, two corresponded to rs1079597 and rs6277, and two that were not reported in the NCBI-SNP located at position 113425553 and 2165110. Besides, only the polymorphism at position 2,165,110 has significance in the association of the disease (p= 0,000334). As well as the association found between the polymorphism 113.425.553 position and the current age of the patients (p=0.044). Additionally, none of the polymorphisms represents a risk for developing schizophrenia in the Ecuadorian population. The present study provides the groundwork for future research on the development of schizophrenia in Ecuador